Personal Hygiene and Personal Protective Equipment Use Affect Irritan Contact Dermatitis: A Sectional Cross Study - Anggi Yuda Pratama; Irma Yasmin; Rina Purnamasari (Future Science, 2024)
Irritant contact dermatitis occurs due to exposure of the skin to various substances that are irritants. Lack of compliance with personal hygiene practices and personal protective equipment (PPE) regulations can cause contact dermatitis. This research aims to determine the relationship between personal hygiene and the use of personal protective equipment and the incidence of irritant contact dermatitis in tofu factory workers. This observational quantitative study used a cross-sectional design. This study included 33 samples from a tofu factory in Dadirejo Village, Pati, using a purposive sampling method based on predetermined inclusion and exclusion criteria. Between-group comparisons were conducted using the Chi-Square test. There was a significant relationship between personal hygiene and the use of personal protective equipment and the incidence of irritant contact dermatitis, with p-values of 0.001 and 0.000. The conclusion is that there is a significant relationship between personal hygiene and the use of personal protective equipment by tofu factory workers in Dadirejo Village, Pati Regency.